Epitope analysis of antibodies recognising the cell proliferation associated nuclear antigen previously defined by the antibody Ki-67 (Ki-67 protein). - Kubbutat, M H (1994)
AIMS--To elucidate the fine specificities of the antibodies MIB 1 and MIB 3 and of additional monoclonal antibodies which also recognise the Ki-67 protein (MIB 5, IND.64, JG-67-2a). METHODS--Different parts of the Ki-67 protein cDNA were expressed in Escherichia coli. Bacterial lysates were separated by sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) and blotted on to nitrocellulose. Additionally different peptides were synthesised on a membrane support (SPOT-Blot). The immunoreactivity of the antibodies with the recombinant proteins and the immobilised synthetic peptides, respectively, was analysed. A competition enzyme linked immunosorbent assay (ELISA) using a soluble synthetic peptide was also performed. RESULTS--The epitopes of all antibodies tested were contained within the same region of seven amino acids. The antibodies MIB 1 and MIB 3 required the five amino acid sequence FKELF for binding, whereas Ki-67, JG-67-2a, MIB 5 and IND.64 detected the sequence FKEL. CONCLUSIONS--It is concluded that the amino acid sequence FKELF represents an immunodominant area of the Ki-67 protein and that there is no correlation between the ability to detect the Ki-67 protein in paraffin wax sections irradiated with microwaves and the epitopes recognised by the antibodies.